2017
DOI: 10.1007/s40962-017-0178-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co and Ni Addition on the Microstructure and Mechanical Properties at Room and Elevated Temperature of an Al–7%Si Alloy

Abstract: Increasing environmental demands are forcing the automotive industry to reduce vehicle emissions by producing more light-weight and fuel efficient vehicles. Al-Si alloys are commonly used in automotive applications because of excellent castability, high thermal conductivity, good wear properties and high strength-to-weight ratio. However, most of the aluminium alloys on the market exhibit significantly reduced strength at temperatures above 200°C. This paper presents results of a study of the effects of Co and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 18 publications
0
13
0
2
Order By: Relevance
“…Bogdanoff et al [14] showed that the combined addition of cobalt (Co) and Ni improved the mechanical properties of a cast Al-Si alloy at elevated temperatures with a 32% improvement of UTS at 230 • C, this improvement could be a result of dispersion strengthening or due to higher degree of contiguity in the 3D network of Co-and Ni-rich phases and eutectic Al-Si. Florian et al [15] investigated the effect of Ni on the high-temperature strength of Al-Si cast alloys; the strength can be increased at 250 • C, Al 3 Ni phases stabilized the Al-Si eutectic network.…”
Section: Introductionmentioning
confidence: 99%
“…Bogdanoff et al [14] showed that the combined addition of cobalt (Co) and Ni improved the mechanical properties of a cast Al-Si alloy at elevated temperatures with a 32% improvement of UTS at 230 • C, this improvement could be a result of dispersion strengthening or due to higher degree of contiguity in the 3D network of Co-and Ni-rich phases and eutectic Al-Si. Florian et al [15] investigated the effect of Ni on the high-temperature strength of Al-Si cast alloys; the strength can be increased at 250 • C, Al 3 Ni phases stabilized the Al-Si eutectic network.…”
Section: Introductionmentioning
confidence: 99%
“…As the Ni content of the alloy increased, the grain size is observed to increase up to 16.25 μm in Cu-Fe-Ni alloy coatings element and this effect is may be caused by the formation of Cu-rich intermetallic prior to the nucleation of α-Fe dendrites [22]. By increasing the Ni content, This little nodule structure also changes to globular structure [23].…”
Section: Fig 4 Surface Morphology Of Cu-fe-ni Alloys Without and With...mentioning
confidence: 98%
“…Zatezna čvrstoća se povećava sa smanjenjem veličine zrna. Za ispitivani materijal razlika u porastu vrednosti pothlađenja od 0,1ºC/s do 1,8ºC/s povećava zateznu čvrstoću za oko 15 MPa [10,11]. Formirana mikrostruktura u leguri Al-8wt%Si-3wt%Cu pripada tipičnoj nemodifikovanoj livenoj strukturi koja se sastoji od aluminijumske matrice, Al-Si i Al-Si-Cu eutektika (slika 5).…”
Section: Slika 4 -Efekat Brzine Hlađenja Na Vrednosti Pothlađenja Vre...unclassified